The mechanism of activation of a [NiFe]-hydrogenase by electrons, hydrogen, and carbon monoxide. - Lamle, SE; Albracht, S; Armstrong, F (2005)
Activation of the oxidized inactive state (termed Unready or Ni(u)) of the [NiFe]-hydrogenase from Allochromatium vinosum requires removal of an unidentified oxidizing entity [O], produced by partial reduction of O(2). Dynamic electrochemical kinetic studies, subjecting enzyme molecules on an electrode to sequences of potential steps and gas injections, establish the order of events in an otherwise complex sequence of reactions that involves more than one intermediate retaining [O] or its redox equivalent; fast and reversible electron transfer precedes the rate-determining step which is followed by a reaction with H(2), or the inhibitor CO, that renders the reductive activation process irreversible.